Risk factors of mastectomy skin flap necrosis in immediate breast reconstruction using low abdominal flaps. Issue 5 (2nd September 2016) - Lee, Taik Jong; Oh, Tae Suk; Kim, Eun Key; Suh, Hyunsuk; Ahn, Sei Hyun; Son, Byung Ho; Lee, Jong Won; Cho, Jonghan; Eom, Jin Sup
Abstract: Background: The purpose of this study was to determine the risk factors associated with mastectomy skin flap necrosis during immediate reconstruction with TRAM or DIEP flaps. Methods: This study reviewed 1116 cases of immediate breast reconstruction over 10 years. Patients ranged in age from 29–76 years (average = 45.1 years), and had an average follow-up period of 65.6 months. Thirteen factors (age, BMI (body mass index), smoking habits, diabetes ptosis grade, midclavicle-to-nipple distance, neoadjuvant chemotherapy, free or pedicled flap, mastectomy method, surgeon, stage, axillary dissection, mastectomy weight) known to be associated with mastectomy flap necrosis were retrospectively analysed. The odds ratios of the risk factors were calculated using logistic regression analyses. Results: Mastectomy skin flap necrosis occurred in 247 cases (22.1%). Univariate regression analysis showed that the odds ratio of age, BMI, ptosis grade, midclavicle-to-nipple distance, free flap, mastectomy method, surgeon, stage, and mastectomy weight were significant and the odds ratios determined using multivariate analysis were significant for mastectomy method, surgeon, and mastectomy weight. Conclusion: During breast reconstruction using abdominal tissue, the independent risk factors that affect mastectomy skin flap necrosis include the mastectomy method, surgeon, and the weight of the mastectomy specimen. Awareness of the impact of each risk factor will lead to the modification and individualisation of surgical techniques and continually improve outcomes.